Probing the pathways of free charge generation in organic bulk heterojunction solar cells - Jona Kurpiers (Nature Portfolio, 2018)
Contradictory models are being debated on the dominant pathways of charge generation in organic solar cells. Here Kurpiers et al. determine the activation energy for this fundamental process and reveal that the main channel is via thermalized charge transfer states instead of hot exciton dissociation.